2016
DOI: 10.1515/amm-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Properties and Microstructure of the Plastically Deformed Alloy Inconel®718, Manufactured by Plastic Working and Direct Metal Laser Sintering

Abstract: Nickel superalloys as Inconel® are materials widely used in the aerospace industry among others for diffusers, combustion chamber, shells of gas generators and other. In most cases, manufacturing process of those parts are used metal strips, produced by conventional plastic processing techniques, and thus by hot or cold rolling. An alternative technology allowing for manufacturing components for jet engines is the technique of 3D printing (additive manufacturing), and most of all Direct Metal Laser Sintering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ni-based superalloys are a wide group of materials subjected to friction welding. There are two broad categories of nickel alloys: precipitation-hardened alloys and solid-solution-strengthened alloys [ 31 , 32 ]. Nickel alloys in both categories can be welded using common processes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ni-based superalloys are a wide group of materials subjected to friction welding. There are two broad categories of nickel alloys: precipitation-hardened alloys and solid-solution-strengthened alloys [ 31 , 32 ]. Nickel alloys in both categories can be welded using common processes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Recently, Dai et al 25 reported that the laser additive manufacturing (LAM)-fabricated Ti-6Al-4V has worse corrosion resistance (refers to anodic dissolution rate at low current densities) than the commercial Grade 5 alloy owing to the larger amount of acicular martensite and less β-Ti, which shed light on the anodic behavior distinctions of Ti-6Al-4V alloy fabricated by LAM and other methods. Analogously, owing to the different microstructural features of Inconel 718 produced by LSF and forging methods (as proved by References 26,27), it is reasonable to believe that their anodic dissolution behaviors are different. Considering that the microstructural features play a significant role in the processing results of ECM, it is necessary to investigate the anodic dissolution behaviors of the LSF-produced and wrought Inconel 718.…”
mentioning
confidence: 95%